Assessment of the Risks of Occupational Diseases of the Passenger Bus Drivers - Vasyl Golinko; Serhiy Cheberyachko; Oleg Deryugin; Olena Tretyak; Olga Dusmatova (Safety and Health at Work, 2020)
Background: The working conditions of bus drivers are difficult; they lead to occupational diseases and require careful study, particularly in Ukraine. The objective of the article is the description of occupational health risks of passenger bus drivers that lead to deteriorating health. Methods: The risk assessment was performed using a modified Risk Score method, which allowed determining the generalized level of danger to the driver's health. The hygienic hazards level was assessed as based on Stevenson's law, which was generalized later. Results: Based on the modification of the Risk Score method, it was possible to depart from expert assessments method of the risk level and calculate the general indicator based on the degree of dependence of the impact on the human body on its intensity, proposed by V. Minko. This allows objective determining of the impact of hygiene hazards on the health of the driver and to predict the occurrence of occupational diseases associated with the cardiovascular system, musculoskeletal system, and partial or complete disability due to the accumulation of emotional fatigue. The hazard assessment was carried out for three brands of passenger buses common in Ukraine, in which the driver is exposed to the dangers of fever, vibration, noise, harmful impurities in the bus cabin, and emotional load. Conclusion: The health of drivers in the cabins of passenger buses is most affected by hygiene hazards: fever, vibration, and emotional stress. The generalized level of risk is calculated by the modified method of Risk Score is 0.83; −0.99, −0.92 respectively.